Association of bevacizumab and stroke in ovarian cancer: a systematic review and meta-analysis - Song, Li; Liu, Yan; Chen, Zhixin; Li, Zeyan; Zhu, Shiqin; Zhao, Yingjie; Li, Huihui (Frontiers in Neuroscience, 2023)
Background The prognosis for patients with ovarian cancer is bleak. Clinical trials have shown the efficacy of bevacizumab in ovarian cancer treatment. However, life-threatening strokes may limit the usage of bevacizumab and require specific follow-up strategies. This study aims to systematically evaluate the risk of stroke of bevacizumab treatment in ovarian cancer. Methods We retrieved all relevant articles published up to December 4th, 2022, from Embase, PubMed, Web of Science, and the Cochrane Library. The risk of stroke in patients with ovarian cancer treated with bevacizumab combined with chemotherapy was analyzed. Meta-analysis was performed using the Stata 17 software and R 4.2.1 program. Results Six randomized controlled trials (RCTs) of bevacizumab combined with chemotherapy or chemotherapy for ovarian cancer and six single-experimental-arm trials were included in this study. The meta-analysis showed a pooled risk ratio (RR) of 2.14 [95% confidence interval (CI): 0.88–7.99] for patients with ovarian cancer treated with bevacizumab combined with chemotherapy. Subgroup analyses showed that the incidence of stroke-related adverse events in the carboplatin + paclitaxel + bevacizumab group was 0.01% (95% CI: 0.00–0.01, p < 0.01). The incidence of stroke-related adverse events was 0.01% (95% CI: 0.00–0.01, p < 0.01) in patients aged ≥60. The incidence of stroke caused by cerebral ischemia and cerebral hemorrhage was 0.01% (95% CI: 0.01–0.02, p = 0.27) and 0.01% (95% CI: 0.00–0.01, p < 0.01), respectively. Conclusions This meta-analysis indicates that chemotherapy combined with bevacizumab may not increase the incidence of stroke in patients with ovarian cancer. However, stroke-related adverse events may be higher in older patients. Cerebral hemorrhage might cause the incidence of stroke more than cerebral ischemia. Systematic review registration PROSPERO (CRD42022381003).